Effects of a glyphosate-based herbicide on Fucus virsoides (Fucales, Ochrophyta) photosynthetic efficiency. (December 2018) - Falace, Annalisa; Tamburello, Laura; Guarnieri, Giuseppe; Kaleb, Sara; Papa, Loredana; Fraschetti, Simonetta
Abstract: Herbicides are increasingly recognised as sources of water pollution. Glyphosate-based herbicides (GBHs) are widely used because of their low cost and high effectiveness. By measuring the photosynthetic efficiency of Fucus virsoides fronds exposed to a GBH (Roundup® Power 2.0), we investigated the effect of a continuous exposure (6 days) and the potential of recovery after a short exposure (24 h). Both experiments were carried out combining GBH with and without nutrient enrichment, simulating a runoff event. A factorial experimental design allowed us to assess the potential of interactions between GBH and nutrients, which are likely to co-occur in coastal areas. Our results show deleterious effects of GBH at low concentration on F. virsoides, independently from the duration of exposure and the presence of nutrients. Graphical abstract: Image Highlights: We tested the effects of glyphosate-based herbicide (GBH) on Fucus virsoides (Ochrophyta). The photosynthetic efficiency of Fucus was reduced by 95% after 6 days of exposure to GBH. Fucus showed irreversible damage even with short time of exposure to GBH (1 day). The use of herbicides on land might drive the reduction of marine macroalgal communities. Land-sea planning in ecosystem-based management is a priority. Abstract : The use of herbicides on land might represent an underestimated threat for coastal systems, as suggested by the irreversible impact on the macroalgae Fucus virsoides observed after a short experimental exposure to a common glyphosate-based herbicide.